Monitoreo y evaluación ambiental en un bosque prístino del cerro Tambo - Provincia de Moyobamba - Soplín Roque, Henry Alexander (2003)
The objective of this study is to provide information of the climate, of the forest resources and its quantification, to provide basic information that allows us to elaborate the Plan of Handling Integral for the Areas of Reduction of the Forest of Protection Alto Mayo. The study area includes Forests High Premontane and Forests Heaths that correspond to 10 places that are along a pending altitudinal from the 1200 - 1589 m a.s.l. in the Hill Tambo, County and District of Moyobamba. The climate of the study area was registered in the Digital Meteorological Station, installed in the western slope of the Hill Tambo to an altitude 1410 m a.s.l. being determined that the annual total precipitation was of 1876.4 mm/year and the temperature averages yearly of 19.4 °C. In the parcels of the Forest High Premontane and Forest Heath information was collected on it structures, composition florística (the height, covering of the canopy, species and families) and characteristic of the floor (number of horizons, texture, depth, pH). The differentiation of the characteristics of floors was carried out with the help of the physical and chemical properties of the different horizons. The abundance stems/ha-1, area basal m2/ha-1, biomass air t/ha-1, it was calculated using empiric equations of OGAWA et al. (1965). In the parcels of the Forest High Premontane was determined that the trees reached a maximum height of 22-31 m, the abundance, the basal area and the air biomass varied of 2103.1 - 5174.77 stems/ha-1, 22-51 m2/ha-1 and of 100-300 t/ha-1 respectively; while in the Forest Dense Heath the trees reached a height of 12-14 m and of 5-7 m of height in the Forest Open Heath, the abundance and the basal area calculated for the Forest Heath varied of 2291.02 - 9277.16 stems utter/ ha-1 and of 1.69-17 m2/ ha-1 and the biomass estimated for the Forest Open and Dense Heath they reported values among 2.4 -15.2 and of 31-43 tn/ha-1 respectively. The analysis of the samples of disks coming from the Forest High Premontane and Heath determined a rhythm of seasonal growth, the proportions of growth of trees of the studied forest were not significantly different, presenting a half annual increment (IMA) of 0.6 - 2.0 mm/año. In the Forest High Premontane met trees with a bigger age to 150 years; while the Forests of Open and Dense Heaths turned out to not have ages bigger to 46 years. The content of important elements in the chemistry of the floor present in the vegetation of the Forest High Premontane and Forest Heath didn't show a difference resaltante, since the presented quantities are very similar. The present aluminum in the floor samples doesn't have bigger incidence since in the distribution of these types of vegetation the different horizons of the parcels they contain the same concentration level (among stocking and high), finally we can suppose that the distribution is due to factors of formation of the floor non treaties in this study.